Questionários de sono de Richards Campbell Português - Brasil (RCSQ-PT- BR) para pacientes internados em unidades de terapia intensiva: adaptação transcultural, consistência interna e confiabilidade inter-avaliador - Varella, Natália (2020)
Sleep disorders are frequent in patients in the intensive care unit (ICU). The Richards-Campbell sleep questionnaire (RCSQ) is among the most used questionnaires for sleep evaluation in English for ICU inpatients. However, the lack of psychometric evaluations of the RCSQ in Portuguese still precludes its application in ICU in Brazil. Aims: To perform the cross-cultural adaptation of RCSQ and to eval its internal consistency, interrater reliability, and measurement error in ICU inpatients. Methods: The study enrolled 113 inpatients at medical/surgical ICU in Curitiba, Brazil. The RCSQ was first translated to Portuguese-Brazil according to the principles of good practice for the translation and cultural adaptation process for patient-reported outcomes and then applied in 30 inpatients. The final version (RCSQ-PT- Br) was applied to measure content validity (83 inpatients; 47 men [56.6%], 60.4 ± 14.2 years), and interrater reliability and measurement error (subset of 53 inpatients). Internal consistency of the RCSQ-PT-Br was estimated using Cronbach's a; interrater reliability (2 independent rates) was assessed using the single measurement, absolute agreement, two-way random effects model (ICC2,1). Results: Group-average RCSQ-PT-Br total score was 46.9 ± 26.7 (range 3.4– 98.8). The RCSQ-PT-Br total score showed good content validity (Cronbach's ! = 0.850 95%CI = [0.789–0.897]) and excellent interrater reliability (ICC2,1 = 0.840 95% CI = [0.739–0.904]). Measurement error was low (standard error of mean = 11 mm, mean difference = 30 mm). Conclusions: The RCSQ-PT-Br is a valid and reliable instrument to evaluate the sleep of patients hospitalized in the ICU in Brazil.